THE CORRELATION BETWEEN SPEAKING ANXIETY AND SPEAKING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS - Aji Tamara Putra; Amalia Hasanah; Deta Desvitasari (Didascein : Journal of English Education, 2023)
Speaking becomes a crucial ability that must be mastered in communication. This is quantitative research with a correlational design which aimed to find out whether or not there was a significant correlation between students’ speaking anxiety and their speaking achievement and the contribution of speaking anxiety to their speaking achievement. The population of this research was all of the eighth-grade students of SMPN 1 Tanjung Raja with a total number of 128 students. However, there were only 32 students involved as the sample in this research taken by using stratified random sampling. By using oral Proficiency categories, students‘ speaking achievement was scored in terms of the six sub-skills of grammar, vocabulary, fluency, pronunciation, comprehension, and task. Furthermore, Public Speaking Classroom Anxiety Scale (PSCAS) questionnaire developed used to measure speaking anxiety containing 17 items. Pearson Product-Moment was used to find out the correlation between variables. The result showed that there was no significant correlation between students speaking anxiety and their speaking achievement with r= (.177) lower than r-table (.349) and the level of probability (p) significance (.332) was more than (.05). It indicated that H0 was accepted and Ha was rejected. This study could have implications for English language teachers, students, and future researchers.